1986
DOI: 10.1128/mcb.6.11.3900
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a molecularly cloned human c-src oncogene by using a replication-competent retroviral vector.

Abstract: We studied the expression of a molecularly cloned human c-src gene, c-src-1, localized on chromosome 20, whose coding region consists of 11 exons and spans a 19.5-kilobase (kb) distance. Using a replication-competent retroviral vector derived from molecularly cloned Rous sarcoma virus DNA (pSRA-2), we obtained two constructs: one (pSR-CS) carrying the unmodified human c-src coding sequence and another (pSR-CVS) with a chimeric gene formed between the human c-src gene and the carboxy-terminal 12-amino acid v-sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…For Src mutant assays, cells were triple transfected for 24 h with ID1pGL, SV40pRL plus PCI vectors containing wild-type human Src, dominant-negative human SrcK298M (provided by Dr. Don Fujita, University of Calgary, Alberta, Canada), or constitutively active chicken SrcY527F (provided by Dr. June Zhou, University of California Davis Cancer Center, Sacramento, CA; ref. 35). Cells were then incubated in fresh 10% FBS DMEM for 18 h followed by serum starvation in DMEM for 6 h. For promoter region assays, cells were triple-transfected for 24 h with Src-Y527F, SV40pRL, plus fulllength ID1pGL or one of seven previously described ID1 promoter 5 ¶ deletion constructs (34).…”
Section: Methodsmentioning
confidence: 99%
“…For Src mutant assays, cells were triple transfected for 24 h with ID1pGL, SV40pRL plus PCI vectors containing wild-type human Src, dominant-negative human SrcK298M (provided by Dr. Don Fujita, University of Calgary, Alberta, Canada), or constitutively active chicken SrcY527F (provided by Dr. June Zhou, University of California Davis Cancer Center, Sacramento, CA; ref. 35). Cells were then incubated in fresh 10% FBS DMEM for 18 h followed by serum starvation in DMEM for 6 h. For promoter region assays, cells were triple-transfected for 24 h with Src-Y527F, SV40pRL, plus fulllength ID1pGL or one of seven previously described ID1 promoter 5 ¶ deletion constructs (34).…”
Section: Methodsmentioning
confidence: 99%
“…As occurs in v-Src (Tanaka and Fujita, 1986), deletion or mutation of Y505 in Lck results in a 'constitutively' active enzyme (Marth et al, 1988). The transmembrane protein tyrosine phosphatase (PTP) RPTPa is thought to dephosphorylate the analogous C-terminal regulatory tyrosine of c-Src and may also dephosphorylate Fyn (Su et al, 1999).…”
Section: Model Of Regulation and Activationmentioning
confidence: 99%
“…In addition, mutationally activated or overexpressed forms of chicken, mouse, and human cSrc have been shown to transform cells in culture under various conditions (Levy et al, 1986;Tanaka and Fujita, 1986;Lin et al, 1995), and mutationally activated human c-Src was found to be highly tumorigenic in chickens when introduced with a viral vector (Tanaka et al, 1990). Taken together, these studies suggested that it was highly likely that aberrant activation of Src kinase activity by mutation or other mechanisms could contribute to the development and progression of some human cancers.…”
Section: Involvement Of C-src Human Cancersmentioning
confidence: 99%
“…c-Src also di ered from v-Src in two important respects: (1) The protein tyrosine kinase activity of cSrc in immunoprecipitates was generally lower than that of v-Src (Iba et al, 1984;Coussens et al, 1985;Tanaka and Fujita, 1986) and (2) c-Src, unlike v-Src, did not cause cell transformation as measured by focus formation in chicken embryo ®broblast cells under conditions of moderate overexpression (Iba et al, 1984;Shalloway et al, 1984;Tanaka and Fujita, 1986). Experiments using chimeric forms of c-Src and v-Src indicated that replacement of the c-Src carboxyterminus with that of v-Src could confer high kinase activity and transforming activity upon the resulting Src chimera (Iba et al, 1984;Tanaka and Fujita, 1986). These experiments, and others, suggested that the carboxy-terminal regions of c-Src and v-Src played important roles in regulating Src activity, as discussed further in the next section.…”
Section: Introductionmentioning
confidence: 99%